A subject-specific anisotropic visco-hyperelastic finite element model of female pelvic floor stress and strain during the second stage of labor - Jing, Dejun; Ashton-Miller, James A.; DeLancey, John O.L. (Journal of biomechanics, 2012)
To develop an improved model representation of the biomechanics of the levator muscles during the second stage of labor and to use a sensitivity analysis to explore the pathomechanics of levator muscle injury. A subject-specific finite element model of human pelvic floor and fetal head was developed based on in vivo MRI data of a fetal head and maternal pelvis. An anisotropic visco-hyperelastic constitutive model employed material parameters estimated from biaxial tests on pelvic floor tissues. Boundary conditions reflected both anatomic constraints and the curve of Carus. A short second stage of labor, scaled to 10min, was then simulated using a single expulsive push made in the absence of levator co-contraction. Large levator stresses occurred near the levator hiatus reaching 9MPa at the pubovisceral muscle enthesis. The dominant principal stresses were located at, and aligned with, the edge of the hiatus. Muscle stretch bordering the levator hiatus was inhomogeneous: the average levator stretch was 3.55 with a high of 4.64 at the pubovisceral muscle enthesis. Decreasing perineal body stiffness by 40%, 50%, and 60% led to reductions in the maximum principal stretch ratio at the pubovisceral muscle enthesis of 8%, 13%, and 18%, respectively. The pubovisceral muscle enthesis and the muscle near the perineal body are the regions of greatest strain thereby placing them at highest risk for stretch-related injury. Decreasing perineal body tissue stiffness significantly reduced tissue stress and strain, and therefore injury risk, in those regions.